2013
DOI: 10.1002/app.39244
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of diether‐ and phthalate‐based Ziegler‐Natta catalysts for copolymerization of propylene and ethylene and terpolymerization of propylene, ethylene, and 1‐butene

Abstract: Copolymerization of propylene and ethylene and terpolymerization of propylene, ethylene, and 1-butene were carried out to compare the characteristics of diether-and phthalate-based Ziegler-Natta catalysts in a reaction system of pilot scale. The ethylene incorporation with the diether-based catalyst was higher but the 1-butene incorporation was lower compared with those of the phthalate-based catalyst. In the case of copolymers from the diether-based catalyst, melting behavior, determined through differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…9 In 1989, the polypropylene catalyst with 1,3-diether as the internal donor was developed by the Himont company. 26 This new internal donor provided a polypropylene catalyst with extremely high activity, isotacticity, hydrogen response, 19 and also narrower MWD without the need for any external donor, 25,26 which breaks the restrictions of the last two generations of catalyst that the polypropylene catalyst, must contain both internal and external donors. It could be considered as the fifth generation of Ziegler-Natta catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 In 1989, the polypropylene catalyst with 1,3-diether as the internal donor was developed by the Himont company. 26 This new internal donor provided a polypropylene catalyst with extremely high activity, isotacticity, hydrogen response, 19 and also narrower MWD without the need for any external donor, 25,26 which breaks the restrictions of the last two generations of catalyst that the polypropylene catalyst, must contain both internal and external donors. It could be considered as the fifth generation of Ziegler-Natta catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…26 Concerning the high activity and high hydrogen response of the diether-based catalysts, it was reported that dietherbased catalysts had a high content of active sites with low regioselectivity, 19 that this effect can be ascribed to chain transfer after the occasional secondary (2,1-) rather than the usual primary (1,2-) insertion. 27 Additionally, the 1,3-diether strongly coordinates to the support and cannot be easily extracted 2 from the catalyst surface on contact with a cocatalyst such as alkylaluminum 19 because the 1,3-diether show higher affinity toward magnesium chloride than to a cocatalyst, and consequently diether-based catalysts make polypropylene having comparatively high isotacticity without an external donor. 16,19 The development of new electron donors (Lewis bases, usually containing oxygen atoms) is one of the chief areas of research in Ziegler-Natta olefin polymerization systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations